The Effect of Product Quality, Brand Image, and Promotion on Customer Loyalty at Rumah Tempe in Pontianak City - Fadia Rachma Octriani; Sumiyati Sumiyati (Economics and Business Journal (ECBIS), 2026)
This study aims to examine the effect of product quality, brand image, and promotion on customer loyalty at Rumah Tempe in Pontianak City. A quantitative approach with an associative research design was used. The sample consisted of 100 Rumah Tempe customers selected through purposive sampling, with the criteria of being at least 17 years old, having made purchases independently, and having purchased the product at least twice. Data were collected through questionnaires using a five-point Likert scale, supported by interviews and documentation. The data were analyzed using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results show that product quality, brand image, and promotion have positive and significant effects on customer loyalty, both partially and simultaneously. Among the three variables, promotion has the strongest influence, indicating that effective promotional activities play an important role in encouraging repeat purchases and customer recommendations. These findings imply that Rumah Tempe should consistently maintain product quality, strengthen its brand image, and optimize promotional strategies to increase customer loyalty in the competitive local snack food market.